Postaccumulation sandstone porosity evolution by mechanical compaction and the effect on gas saturation: Case study of the Lower Shihezi Formation in the Bayan'aobao area, Ordos Basin, China. (May 2020) - Xia, Lu; Liu, Zhen; Cao, Yingchang; Zhang, Wei; Liu, Junbang; Yu, Chunlan; Hou, Yingjie
Abstract: Porosity evolution and reservoir quality are strongly affected by mechanical compaction. However, the compaction-induced porosity reduction process in sandstone reservoirs during the postaccumulation period and its effect on gas saturation remain poorly understood. By studying the sandstones in the Bayan'aobao area, we were able to quantify the porosity evolution and gas saturation variations caused by mechanical compaction during the postaccumulation period through fluid inclusion analysis and mathematical modeling. Moreover, we verified our findings by compaction experiments and geological statistics. Fluid inclusion microthermometry was employed to determine the hydrocarbon accumulation periods, and the highest homogenization temperature of the two-phase aqueous fluid inclusions coexisting with natural gas fluid inclusions, i.e., 115 °C (with a corresponding geological age of 140 Ma), was regarded as the beginning of the postaccumulation stages. With these data, we constructed an inversion evolution model (based on the geologic statistical model of sandstone mechanical compaction) for the postaccumulation period and determined the gas saturation changes (based on compaction porosity evolution). The modeling results indicate that the sandstone porosity decreased greatly during postaccumulation subsidence and increased slightly during late-stage uplift, while the gas saturation increased with both the porosity decrease during the postaccumulation subsidence and the porosity increases during the later uplift. The modeling results of subsidence are concordant with the compaction experiments, which also show that the larger the initial porosity, the greater the porosity reduction. The uplift modeling results demonstrate that an erosion-induced decrease in burial depth allowed the sandstone porosity to increase, which is supported by some scholars' findings (e.g., Neuzil and Pollock, 1983; Jiang et al., 2004; Zhang, 2013) and by the positive correlation between sandstone porosities and restored geologic unit thicknesses in the study area. However, the inversion modeling indicates that the reason for the porosity rebound in litharenites is that the increase in elastic porosity slightly exceeds the decrease in viscoplastic porosity, which would have been different if the uplift-induced erosion rate had been distinctly lower. Gas production test data and restored geologic unit thicknesses indicate that uplift and erosion may be able to enrich sandstone gas reservoirs to a certain extent, consistent with the calculated gas saturation variation results, but a full understanding of gas saturation evolution awaits further studies. The inversion model can provide a powerful tool for quantitative analysis of the sandstone compaction process during the postaccumulation period, which could be used for reference in other similar regions. Highlights: We studied postaccumulation sandstone porosity evolution by mechanical compaction in quantitative inversion modeling. Compaction-induced porosity reduction differences are revealed in compaction experiments and inversion modeling. Uplift-induced sandstone porosity rebound is indicated by inversion modeling and geological statistics. Porosity increase in response to late-stage uplift would likely promote the enrichment of gas reservoirs.